+0  
 
0
332
2
avatar

Another Algebra 2 question...

Guest Oct 3, 2017
 #1
avatar
0

Solve for x:
(3 x - 2)^2 = (5 x + 1)^2

Take the square root of both sides:
3 x - 2 = 5 x + 1 or 3 x - 2 = -5 x - 1

Subtract 5 x - 2 from both sides:
-2 x = 3 or 3 x - 2 = -5 x - 1

Divide both sides by -2:
x = -3/2 or 3 x - 2 = -5 x - 1

Add 5 x + 2 to both sides:
x = -3/2 or 8 x = 1

Divide both sides by 8:
x = -3/2         or          x = 1/8

Guest Oct 3, 2017
 #2
avatar+27128 
+3

"Use the identity a2-b2=(a-b)(a+b) to solve the problem:  (3x-2)2=(5x+1)2"

 

Rewrite as:  (5x+1)2 - (3x-2)2 = 0

 

Let a = 5x+1 and b = 3x-2

 

(5x+1)2 - (3x-2)2 → (5x+1 - (3x-2))(5x+1 + 3x-2) → (2x + 3)(8x - 1)

 

so (2x + 3)(8x - 1) = 0

 

Hence 2x + 3 = 0   giving  x = -3/2

 

or  8x - 1 = 0  giving  x = 1/8

.

Alan  Oct 3, 2017

15 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.